Proceso logístico en la importación a consumo vía marítima de equipos de audio y video desde China - Solis Martillo, Yuliana (2019)
The present investigation from the profound changes in the environment of companies and sectors that require companies to review their strategies and define their management. Technological, social, cultural, economic and competitive changes influence companies that have to adopt new priorities; that allow us to find a systematic path and capable of guaranteeing better services. Based on the exploratory and descriptive study carried out in the company COTZUL S.A. the problem is shown in the process of importing audio and video equipment, products considered to be of greater importance in their commerce. It can be seen that the company fails to comply with the delivery time of its imported products at the time of its dispatch, which implies a series of processes prior to the nationalization that must be carried out by the import department. It is true that the transit time cannot be manipulated, since it is outside the responsibility of the company, if it is possible to adapt changes within the administrative process of purchases………..